Safety of the PD-1 antibody pembrolizumab in patients with high-grade adverse events under ipilimumab treatment - Bender, Carolin; Enk, Alexander; Hassel, Jessica C. (Annals of oncology, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For permissions, please email: journals.permissionsoup.com.Treatment with immune checkpoint inhibitors frequently leads to immune-related adverse events (irAEs). As patients who have previously experienced high-grade AEs with ipilimumab are excluded from most studies with anti-programmed cell death-1 or anti-programmed cell death ligand-1 antibodies (Abs), there are little data on the safety of sequential therapy in this patient population [2, 3]. However, especially BRAF wild-type melanoma patients are in need of further treatment options after progression with ipilimumab. Hence, we treated patients who had to stop ipilimumab treatment because of a severe autoimmune reaction after complete resolution of symptoms and cessation of the immunosuppressive treatment with the anti-PD-1 Ab pembrolizumab....Data from patients treated with pembrolizumab 2 mg/kg q3w was retrospectively analyzed. Eight of 49 (16.3%) patients had...